Oxygen and carbon metabolism of Zostera muelleri across a depth gradient – Implications for resilience and blue carbon. (5th March 2017) - Ferguson, Angus J.P.; Gruber, Renee; Potts, Jaimie; Wright, Aaron; Welsh, David T.; Scanes, Peter
Abstract: There is growing interest in the role that seagrasses play as 'blue carbon' stores or sinks, and their potential to offset rising CO2 levels in the atmosphere. This study measured primary aspects of the carbon balance (biomass, community metabolism, dissolved organic carbon [DOC] fluxes, seston trapping) across the depth gradient in a Zostera muelleri meadow during the seasonal biomass minimum and maximum. Over the annual estimation, the meadow was neither a sink nor source of carbon, with inputs of seston (∼58% of total inputs) balanced by exports of wrack and DOC. The carbon sink represented by wrack export depends on the nature of the environment where the wrack accumulates; if it reaches subtidal sediments it will largely be remineralised over the annual cycle, whereas between 14 and 26% of the wrack may be preserved if the material is exported to terrestrial environments. The fate of DOC exuded by seagrasses is unknown due to a lack of knowledge about its composition and lability; however, a number of lines of evidence suggest that a large fraction of DOC is mineralised. The net community metabolism (NCM) of the meadow was balanced, indicating that photosynthetic O2 production balanced community respiration and/or the reoxidation of reduced compounds (sulphur and iron) in the rhizosphere. We suggest that a balanced NCM may be the preferred state for Zostera spp. and may limit their occurrence in environments where plants cannot balance the respiratory demand exerted by seston inputs. There was a close coupling between metabolism and biomass, which in turn is forced by antecedent light over the preceding 120 days (the time integration window for antecedent light that best predicted biomass). Increased metabolism with depth and seasonal variation in light is accompanied by a decrease in the above ground:below ground biomass ratio (AGB:BGB). This trend is suggested to be a morphological adaptation that balances the competing requirements of maintaining a neutral plant carbon balance across enrichment and light gradients. Our results suggest that Zostera muelleri may be most important as a 'blue carbon' store (i.e. carbon stored as biomass standing stock), which is therefore vulnerable to degradation if seagrasses are lost.